A Note On Fundamental Core Theorem of The Mulatu Numbers and its fascinating Corollaries. - Lemma, Mulatu; Lord, Keith; Tessema, George (IJRDO -JOURNAL OF MATHEMATICS, 2017)
The Mulatu numbers are sequences of numbers of the form 4, 1, 5, 6, 11, 17, 28, 45, …. The numbers have wonderful and amazing properties and patterns. In mathematical terms, it is defined by the following recurrence relation: Mn= 4